Factors Associated with Intimate Partner Violence and the Utilization of Maternal Health Services: Findings from Nepal Demographic Health Survey 2016. - Acharya, Devaraj; Adhikari, Ramesh; Ranabhat , Chhabilal; Paudel, Radha; Kreps , Gary L.; Bhandari, Tulsi Ram; Bhattarai , Radha; Pathak , Krishna Prasad (Europasian Journal of Medical Sciences, 2021)
Background: Intimate partner violence (IPV)is a public health problem globally and is most common in developing countries. IPV affects more than one-fourth of all women of reproductive age [WRA]. It is most critical during pregnancy. IPV not only affects physical and mental well-being but also leads to negative consequences with birth outcomes. The paper aims to find out the association between background characteristics of participants, IPV, and utilization of maternal health services. Methods: We conducted a secondary data analysis of the Nepal Demographic and Health Survey 2016 to assess the association between IPV and maternal service utilization: ANC visits and institutional delivery. Altogether 1374 WRA were randomly selected. Background characteristics of the WRA and those who experienced IPV were the independent variables and ANC visits and institutional delivery were the dependent variables. Results: Data showed that 26 percent of the WRA had faced at least one form of IPV, 68 percent had visited health facilities at least four times for ANC check-ups during pregnancy, and the rate of institutional delivery was 61 percent. There were associations among IPV with ANC visits and institutional delivery (p<0.001). Age group, educational level, ethnicity, number of children, residence setting, and wealth status of the WRA were significantly associated with ANC visits and institutional delivery (p<0.001). Conclusions: IPV, educational level, and socio-economic status of WRA were significant predictors for maternal health service utilization. Policymakers should incorporate these significant predictors during planning and intervention programs as well. DOI: https://doi.org/10.46405/ejms.v3i2.279